Pengaruh Media Pembelajaran Quizlet terhadap Hasil Belajar Fikih Kelas 5 - Latinisah, Nia; Susanti, Cela Petty (Universitas Muhammadiyah Magelang, 2026)
One important field in Islamic religious education is fiqh, which studies Islamic laws concerning human relationships with Allah and with one another. Research conducted in class V at MI Al-Kausar Ponorogo shows that student learning achievements are below the minimum competency standard. This is due to a lack of understanding among students, a learning approach dominated by lectures, and a lack of variety in learning media. As a result, students quickly become bored and inactive in class. To overcome this problem, researchers suggest using Quizlet as a learning tool that makes fiqh lessons more interactive, independent, and enjoyable for students. This study used a quantitative approach and employed a real design of a pre-test and post-test control group. Simple random sampling was used to select 51 students. Data were collected using multiple-choice tests and analysed using SPSS 25. The results of the analysis using the Mann-Whitney nonparametric test show that Ho is rejected and Ha is accepted, with a Sig (2-tailed) value of 0.011 < 0.05. Thus, the evidence shows that Quizlet is effective in improving students' understanding of Fiqh. The researcher suggests that teachers use it as a creative tool and students use it as a way to study independently.